Editorial Special Issue: Logistics, networks and sustainability in freight transport - Zamparini, Luca (European Journal of Transport and Infrastructure Research, 2007)
The papers in this Special Issue provide several analyses and descriptions of the relevance of logistics, networks and sustainability in the recent evolution of freight transport flows at the local, national, and global levels. This phenomenon has been determined by several causes. First, the augmented GDP per capita in developed economies has stimulated the demand for an ever-increasing amount and variety of goods. Moreover, a significant share of the productive processes has been outsourced from the developed countries towards the developing ones. The economic reasons that have fostered this delocalization can be traced back to lower labour and investment costs in the latter countries, together with the decrease in unit transport costs. There has consequently been an increase in the complexity of existing freight transport networks and the emergence of new ones (Van Geenhuizen et al., 2007). This evolution has partly been related to the behaviour of logistics firms that, faced with an ever-rising level of competition, have been looking for alternative transport networks involving the implementation of peculiar transport means or of efficient intermodal systems (Beuthe et al., 2004). Moreover, as was mentioned above, new transport networks have emerged on the basis of evolving consumers’ demands and productive processes. This has, on the one hand, implied the urge for logistics firms to reconsider their strategic decisions (Brewer et al., 2001; De Kok and Graves, 2003) and, on the other hand, the opportunity for local and national administrations to take advantage of the international and/or intercontinental hubs of freight transport networks located within their territories (Banister, 2002).